2003
DOI: 10.1113/jphysiol.2002.029306
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the myosin phosphatase targeting subunit and CPI‐17 during Ca2+ Sensitization in Rabbit Smooth Muscle

Abstract: Myosin phosphatase (MLCP) plays a critical regulatory role in the Ca2+ sensitivity of myosin phosphorylation and smooth muscle contraction. It has been suggested that phosphorylation at Thr695 of the MLCP regulatory subunit (MYPT1) and at Thr38 of the MLCP inhibitor protein CPI‐17 results in inhibition of MLCP activity. We have previously demonstrated that CPI‐17 Thr38 phosphorylation plays an important role in G‐protein‐mediated inhibition of MLCP in tonic arterial smooth muscle. Here, we attempted to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

30
245
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(280 citation statements)
references
References 44 publications
30
245
5
Order By: Relevance
“…8), but the addition of carbachol (within 30 s) immediately phosphorylated CPI-17 at Thr 38 , and the phosphorylation levels were well maintained for over 10 min during the carbachol stimulation. These results are consistent with previous results (24,53) obtained in other smooth muscles and suggest that CPI-17 phosphorylation may play a pivotal role in the carbachol-induced Ca 2ϩ sensitization in rat ileum. Furthermore, in the ileal smooth muscle, Y-27632 inhibited the carbachol-induced increase in CPI-17 phosphorylation by ϳ30% (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…8), but the addition of carbachol (within 30 s) immediately phosphorylated CPI-17 at Thr 38 , and the phosphorylation levels were well maintained for over 10 min during the carbachol stimulation. These results are consistent with previous results (24,53) obtained in other smooth muscles and suggest that CPI-17 phosphorylation may play a pivotal role in the carbachol-induced Ca 2ϩ sensitization in rat ileum. Furthermore, in the ileal smooth muscle, Y-27632 inhibited the carbachol-induced increase in CPI-17 phosphorylation by ϳ30% (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Incubation of the tissue for 5-15 min with carbachol significantly increased MYPT-1 phosphorylation, but its extent was very small (less than 20%). These results coincide with those of the most recent studies in the rabbit portal vein and vas deferens (24) and the rabbit femoral artery (53). Therefore, we concluded that MYPT-1 phosphorylation does not play an essential role in the Ca 2ϩ sensitization induced by receptor stimulation in rat ileum.…”
Section: Discussionsupporting
confidence: 81%
“…Several kinases purified from smooth muscles, such as PKC␣͞␦, ZIPkinase, and integrin-linked kinase, activate CPI-17 by phosphorylation at Thr-38 (15)(16)(17). Phosphorylation of CPI-17 at Thr-38 in smooth muscle cells occurs in response to various agonists, such as histamine, endothelin-1, and angiotensin II, in parallel with induction of myosin phosphorylation and contraction (18,19). On the other hand, phosphorylation of CPI-17 is reversed during vasodilation induced by nitric oxide production (20).…”
mentioning
confidence: 99%
“…Agonist-induced Ca 2+ sensitization is due to inhibition of MLCP activity resulting in an increased ratio of MLCK/ MLCP activity [21]. It has been suggested that two different pathways lead to MLCP inhibition, which operate through Rho and PKC, respectively [5,6,11,14,18]. Activation of G q/11 -coupled M 3 receptors, via stimulating phospholipase C (PLC) activity, produces the second messenger diacylglycerol (DAG) which activates PKC, and this causes phosphorylation of CPI-17 (PKC-activated 17 kD inhibitor protein) to inhibit MLCP activity [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that two different pathways lead to MLCP inhibition, which operate through Rho and PKC, respectively [5,6,11,14,18]. Activation of G q/11 -coupled M 3 receptors, via stimulating phospholipase C (PLC) activity, produces the second messenger diacylglycerol (DAG) which activates PKC, and this causes phosphorylation of CPI-17 (PKC-activated 17 kD inhibitor protein) to inhibit MLCP activity [9,11]. Although the small G-protein Rho is activated by G 12/13 -type G-proteins, recent studies have suggested that it is activated by G q/11 -type Gproteins as well [1,32].…”
Section: Discussionmentioning
confidence: 99%